2006
DOI: 10.1152/ajprenal.00118.2006
|View full text |Cite
|
Sign up to set email alerts
|

BK channels in the kidney: role in K+secretion and localization of molecular components

Abstract: Although it is generally accepted that ROMK is the K(+) secretory channel in the mammalian distal nephron, recent in vitro and in vivo studies have provided evidence that large-conductance Ca(2+)-activated K(+) channels (BK, or maxi K) also secrete K(+) in renal tubules. This review assesses the current evidence relating BK channels with K(+) secretion. We shall consider the component proteins of the BK channel, their localization with respect to segment and cell type, and the electrophysiological forces invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
70
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 111 publications
(166 reference statements)
2
70
0
Order By: Relevance
“…Indeed, our group recently demonstrated that genetic ablation of TRPV4 abolishes flow-dependent [Ca 2ϩ ] i responses in microdissected distal nephron preparations (12). Consistently, flow-dependent K ϩ secretion in the distal nephron, a Ca 2ϩ -dependent process utilizing the maxi-K channel (13,14), is absent in TRPV4 knock-out animals (15).…”
Section: ؉mentioning
confidence: 85%
“…Indeed, our group recently demonstrated that genetic ablation of TRPV4 abolishes flow-dependent [Ca 2ϩ ] i responses in microdissected distal nephron preparations (12). Consistently, flow-dependent K ϩ secretion in the distal nephron, a Ca 2ϩ -dependent process utilizing the maxi-K channel (13,14), is absent in TRPV4 knock-out animals (15).…”
Section: ؉mentioning
confidence: 85%
“…27 Interestingly, in many cells, BK channels are described to control different steps of the secretary process. 9,[28][29][30] These observations prompted us to investigate whether BK channels could control the tumor growth through a modulation of chemokine expression (Fig. 4).…”
Section: Bk Channels Modulate Ccl2 and Ccl20 Chemokine Expression In mentioning
confidence: 99%
“…In the ASDN, K + is taken up by basolateral Na + /K + -ATPases and is excreted by luminal renal outer medullary K + (ROMK) and large conductance Ca 2+ -activated K + (BK) channels. 2,[7][8][9] The electrochemical driving force for K + secretion is provided by activation of apical epithelial Na + channels (ENaCs). 1,10 In the ASDC, K + is taken up across the basolateral plasma membrane by the Na -cotransporter type 1.…”
mentioning
confidence: 99%